Comparison of Nucleosome Landscapes Between Porcine Embryonic Fibroblasts and GV Oocytes - Minjun Zhao; Shunran Zhao; Zhaoqi Pang; Chunhui Jia; Chenyu Tao (Animals)
(1) Background: Nucleosomes represent the essential structural units of chromatin and serve as key regulators of cell function and gene expression. Oocytes in the germinal vesicle (GV) stage will later undergo meiosis and become haploid cells ready for fertilization, while somatic cells undergo mitosis after DNA replication. (2) Purpose: To furnish theoretical insights and data that support the process of cell reprogramming after nuclear transplantation. (3) Methods: We compared the nucleosome occupancy, distribution, and transcription of genes between two types of cells: fully grown GV oocytes from big follicles (BF) and somatic cells (porcine embryonic fibroblast, PEF). (4) Results: The nucleosome occupancy in the promoter of BF was 4.85%, which was significantly higher than that of 3.3% in PEF (p < 0.05), and the nucleosome distribution showed a noticeable increase surrounding transcriptional start sites (TSSs) in BF. Next, we reanalyzed the currently published transcriptome of fully grown GV oocytes and PEF, and a total of 51 genes in BF and 80 genes in PEF were identified as being uniquely expressed. The nucleosome distribution around gene TSSs correlated with expression levels in somatic cells, yet the results in BF differed from those in PEF. (5) Conclusion: This study uncovers the dynamic nature and significance of nucleosome positioning and chromatin organization across various cell types, providing a basis for nuclear transplantation.